Patterns of species richness for blackflies (Diptera: Simuliidae) in the Nearctic and Neotropical regions - McCreadie, John William; Adler, Peter H.; Hamada, Neusa (Ecological Entomology, 2005)
1. Patterns of simuliid species richness were examined over a variety of scales at 532 stream sites in the Nearctic (394) and Neotropical (138) regions. In Nearctic streams, species richness of immature blackflies both within and across ecoregions and over two seasons was examined. Stream variables at each site included seston, width, depth, velocity, discharge, conductivity, pH, dissolved oxygen, water temperature, dominant streambed-particle size, canopy cover, and riparian vegetation. These variables were subjected to a principal component analysis and derived principal components were related back to richness, using regression analysis. At the level of the stream reach, richness was not highly correlated with single-point measurements of stream conditions. 2. Using data from both Nearctic and Neotropical sites, the effect of regional richness on local richness was examined. As regional richness increased, local diversity reached an asymptote in which further increases in regional richness were not matched by increases in local richness. Hence, simuliid communities are best described as saturated (type II) communities, consistent with the current view of lotic communities as non-equilibrium systems. 3. The well-established pattern of greater species richness in tropical regions was not observed in this study. To the contrary, blackfly richness is higher in temperate streams than in tropical streams at both local and regional scales. © 2005 The Royal Entomological Society.
Keywords: Community Composition; Environmental Factor; Nearctic Region; Neotropical Region; Species Richness; Stream; Diptera; Nearctic; Riparia; Simuliidae